An Investigation of Receptive and Productive Morphological Knowledge of Derivational Suffixes in Turkish Learners of English - Tosun, Sibel; Onur, Fulya Eslek (Journal Language Teaching & Learning, 2021)
Morphological awareness (MA) has been regarded as a profoundly important aspect of enhancing both vocabulary breadth and depth. As one of the predictors of morphological competence, knowledge of derivational suffixes has a crucial place among all morphemes because they have the ability to change word class. This descriptive study, which employed a quantitative approach, aimed to investigate students' receptive and productive knowledge of derivational class-changing suffixes and to identify to what extent they can produce appropriate derivatives in different word classes. Predictive roles of receptive and productive MA on writing achievement are also a subject of the current study. To achieve the purpose, 50 undergraduate EFL students studying at the School of Foreign Languages at a state university, whose ages ranged between 18 and 22 participated in the study. The results of the study indicated that the participants were significantly better at the receptive task than in productive task. It has also been found that productive MA uniquely predicts writing performance scores. The current study is noteworthy in that it aims to shed light on the strengths and weaknesses of the learners' morphological knowledge as well as provide insights for similar settings on the areas to specifically focus on while teaching derivational suffixes. (C) Association of Applied Linguistics. All rights reserved
Keywords: Morphological awareness; Derivational suffix; Word class; Receptive and productive knowledge; Vocabulary knowledge; Writing performance